Analysis of Outpatient Waiting Times at the M. Natsir Regional General Hospital, Solok City in 2024 - Agustini, Tiara Tri; Fadila, Azhariah; Setyowati, Bonita Dwi; Rahmadani, Destia; Ependri, Fitrah Khairani; Qamara Nur, Syamsadiya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Hospitals are important health service centers and are needed to fulfill health needs. This study aims to evaluate the waiting time for ready-made and compounded medicine services based on minimum hospital service standards and their influence on general outpatient satisfaction at the M.Natsir Hospital Pharmacy Installation. This study used a descriptive research design on outpatients who filled prescriptions for finished medicines and compounded medicines. Calculation of waiting time for prescription services for ready-made medicines and compounded medicines is done using a digital clock. The sample taken in the research was 72 respondents. The research results showed that the average waiting time for non-concocted prescription services (19 minutes) and concocted medicines (27 minutes) met the standards set by the SPM for hospitals in the pharmaceutical sector according to the Indonesian Minister of Health NO. 129 of 2008 as well as waiting time standards set by M. Natsir Regional Hospital.